Bottleneck Pelayanan Nifas pada Upaya Penurunan Risiko Kejadian Kematian Ibu di Wilayah Dinas Kesehatan Kota Semarang - Ike Johan Prihatini; Sri Achadi Nugraheni; Sutopo Patria Jati (Jurnal Manajemen Kesehatan Indonesia, 2017)
Maternal and child health was a priority of health program in Indonesia. Maternal Mortality Rate in Semarang was ranked second highest in Central Java. The highest proportion of maternal deaths occurred during puerperium. That’s indicates, there was a problem in a process of maternal health services during puerperium period in health facilities. This study was conducted to examine constraints on health systems that limit range of interventions or health services that were important for postpartum, bottlenecks related to postpartum services in Public Health Center (PHC), especially infrastructure, human resources, access to PHC, post partum visits (KF1 and KF3), as well as quality of post partum services on risk reduction of maternal mortality. This case study used a qualitative approach. Data collection through interviews to five midwives as main informants, 5 midwives coordinator and 5 heads of PHC as informant triangulation. Data analsyis used content analysis method, then assigned priority bottleneck through MCUA (Multiple Criteria Utility Assessment) techniques. WHO's scale-up BNA plan to analyze bottleneck causes. Results showed, there was a bottleneck on childbirth services in PHC. The causes of bottleneck risk reduction efforts of maternal mortality incidence in puerperium period has never been analyzed workload of health personnel in PHC, lack of monitoring and evaluation of an availability infrastructure facilities in PHC, there has not been regular training, especially on delivery until puerperium services, and PHC has not received more detailed and operational information about puerperium so their maternal knowledge about puerperium has not increased much and couldn’t raise mother's awareness to do so. Semarang Public Health Office (Dinas Kesehatan Kota Semarang) needs to conduct periodic monitoring and evaluation implementation of postpartum services and improve quality of childbirth services in PHC.Keywords: Bottleneck analysis, health services, post partum, Primary Health Care, Puskesmas, Maternal Mortality Rate